Eksistensi BUMDes dalam Upaya Meningkatkan Pendapatan Asli Desa (PAD) dan Penguatan Ekonomi Desa di Kecamatan Susukan, Kabupaten Cirebon, Provinsi Jawa Barat - Haniah Hanafie; Agus Nugraha; Masrul Huda (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The establishment of BUMDes to be required for every Village. However, not all BUMDes are in accordance with Permendes No.4 Tahun 2015 there are still BUMDes that do not have any activities at all. The purpose of this study is to examine more deeply about the Existence of BUMDesa in an Effort to Increase Village Original Income (PAD) and Strengthen Village Economy, Susukan District. The concept of Existence, PAD and economic strengthening are used as analytical knifes in research. This study used a qualitative approach. Interviews, observations and documentation review were used as data collection techniques. Descriptive analysis technique is used in processing data by using data analysis procedures proposed by McNabb. Research locations in 4 villages: Susukan, Ujunggebang, Wiyong and Tangkil, Susukan District, Cirebon Regency, West Java Province.The results showed that the existence of BUMDes Subdistrict Susukan was not in line with the expectations of the Act Terms of formality, all four villages had established BUMDesa, but BUMDes of Jembar Jaya in Ujunggebang Village had just started operating in the field of clean water supply business, but had not provided significant benefits. Meanwhile, for the three villages, the BUMDes are not yet running. Special for Susukan Village, although the BUMDes has not carried out activities, it has been able to increase PAD and strengthen the village economy. This is because the Susukan Village Government is able to drive the economy through markets, parking lots and shops and night markets